Modern Technologies for Creating the Thin-film Systems and Coatings - Nikitenkov (InTech, 2017)
Nikolay N. Nlkitenkov finished his studies at the Moscow State University and there defended his candidate and doctoral dissertations in Physics. Currently, he is a professor at Tomsk Polytechnic University. He lectures in the direction of "Modern Methods of Studying Solid Surfaces and Thin Films." He is the researcher and expert in the following directions: modern technologies for creating thin-film systems and coatings; physics of metal-hydrogen systems; and modern research methods of the surfaces and thin films. He has published over 150 articles in these areas, including more than 50 in international journals, with high rating. Development of the thin film and coating technologies (TFCT) made possible the technological revolution in electronics and through it the revolution in IT and communications in the end of the twentieth century. Now, TFCT penetrated in many sectors of human life and industry: biology and medicine; nuclear, fusion, and hydrogen energy; protection against corrosion and hydrogen embrittlement; jet engine; space materials science; and many others. Currently, TFCT along with nanotechnologies is the most promising for the development of almost all industries. The 20 chapters of this book present the achievements of thin-film technology in many areas mentioned above but more than any other in medicine and biology and energy saving and energy efficiency.